Effect of Humic acid and P-Fertilization on P-Forms Distribution Organic / Inorganic in a calcareous Soil: Phosphorous Fractionation (Latakia University Journal -Biological Sciences Series, 2021)
A field experiment was conducted in a calcareous soil (CaCO3 = 49.7%) during 2018 season at Stkheres Research Station in Lattakia to study the Effect of Humic acid (0 and 25 kg K-humate/ha, HA0 and HA25) in the response of maize crop (Tango hybrid) to TSP application (P2O5 46%) as (0 - 30 - 60 - 90 - 120 - 240 kg/ha, P0 to P5). Therefore, the experiment consisted of 12 treatments with three replicates, and plots were completely randomized. Soil samples were taken from the surface layer (0-30 cm) before and after cultivation. Sequential extraction of phosphorous fractions, P-organic and P-inorganic, was carried out using a Headley procedure.Humate increased the amount of inorganic phosphorus extracted by NaHCO3 at the rate of TSP ≥ 180 kg/ha. The increase in NaHCO3-P was obvious in P4HA1 and P5HA1 treatments compared to treatments without humate by about 38% and 27%, respectively. No significant changes were observed in the amount of Pi extracted with 0.5M NaOH when adding humate with low rates of TSP until 60 kg/ha. Phosphorous ions fixed with calcium compounds, extracted by 1M HCL, formed constitute the largest part of the Pi in calcareous soil. Nevertheless, the treatments that received humate decreased the amount of HCl-Pi at every rate of TSP amendment compared to the same TSP- amendment treatment without humate.Humate played an important role in keeping the organic available phosphorous NaHCO3-Po to be similar native-Po (74.2 mg P/kg soil), particularly at a rate of higher than 60 kg TSP/ha. The increased sum of available-Pi and Po associated positively with the organic P which was extracted by NaHCO3, and this relationship was linear R = 0.9515. However, there was a negative relationship between TSP rates and the Residual-Po in this calcareous soil, with or without humate added.